(untitled) (Proceedings of the International Conference on Hospitality and Tourism Management, 2022)
It is expected that concerns or crisis for the overtourism will increase in Japan, in the post pandemic. As countermeasures for the overtourism, such as to provide tourists with visible congestion statuses at sightseeing destinations and guiding tourists to disperse are raised. Then, the present study aims to develop a sightseeing support system that encourages users to go distributed sightseeing through two original functions. One is the function that provide users with visible congestion statuses by utilizing Web-geographic information systems (GIS). The other is that guides users to disperse by utilizing a recommendation system. These functions are implemented by utilizing reviews collected from web tourism medias. The system was developed by integrating social networking service (SNS), Web-GIS, and a recommendation system. Additionally, the system was operated for 12 people for one week in Kamakura City, Kanagawa Prefecture, Japan. And the system evaluated with web questionnaire survey. For operation, 30,357 reviews and 256 sightseeing spots and restaurants information were collected. From the results of questionnaire survey, the system can encourage users to consider desirable seasons or places when they plan to go sightseeing, and to make their interest for sightseeing spots which they did not know until then. Therefore, the system can encourage users to go distributed sightseeing.